The effect of nanoparticle tooth grafts on osteoblast stimulation in the first stages of the bone healing process in Wistar rats compared to the micro-tooth graft technique - Kumala, Ega Lucida Chandra; Fauzia, Malianawati; Junivianti, Hana Salsabila (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: The use of a bone graft in bone regeneration is challenging. Tooth graft material has been used as a bone graft alternative due to its similar composition of organic and inorganic materials close to the bone. Recently, nanotechnology has been used to improve bone graft quality. The osteoconduction rate in the defect area represents the bone graft quality. Purpose: This study aimed to compare the number of osteoblasts using nano-tooth grafts and micro-tooth grafts in Wistar rats. Methods: Wistar rats were divided into six groups: the negative control groups (examined on days 7 and 14), the micro-tooth graft groups (examined on days 7 and 14), and the nano-tooth graft groups (examined on days 7 and 14). The control group received nothing, the micro-tooth group received a micro-size tooth graft, and the nano-tooth graft group received a nano-size tooth graft on the injured femur. Histological observations of osteoblasts were carried out using a light microscope with 1000x magnification. Data were analyzed using one-way analysis of variance and least significant difference tests. Results: On day 7, the nano-tooth graft group showed a higher osteoblast number (11.75) than the micro-tooth graft group (7.5) (p = 0.039). There was no significant difference in the micro-tooth graft group compared to the control (p > 0.05). On day 14, the nano-tooth graft group showed a decrease in osteoblast number close to normal (control) (p > 0.05), while the micro-tooth graft group still experienced significant elevation. Conclusion: Nano-tooth grafts accelerate the stimulation of osteoblasts in the first stages of the healing process compared to micro-tooth grafts.